1959
DOI: 10.1677/joe.0.0190150
|View full text |Cite
|
Sign up to set email alerts
|

Myometrial Responses to the Menstrual Plain-Muscle Stimulant

Abstract: SUMMARY The guinea-pig uterus and strips of human myometrium are stimulated in vitro by ether extracts of menstrual fluid; the guinea-pig uterus is also stimulated in vivo by intravenous or intracardiac injections of the same extracts. The amount of the active material recovered from menstrual fluid probably varies from subject to subject, and in one instance was shown to decrease steadily from the beginning to the end of the menstrual period. The uterine responses in vitro take several forms, all exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1960
1960
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…2. This experiment confirms earlier observations (Pickles, 1959) in that a single addition of menstrual stimulant caused the rhythmical contractions of the preparation to become better co-ordinated and more powerful. Such a response might continue almost indefinitely, but in this instance it was inhibited by the addition of ambucetamide.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…2. This experiment confirms earlier observations (Pickles, 1959) in that a single addition of menstrual stimulant caused the rhythmical contractions of the preparation to become better co-ordinated and more powerful. Such a response might continue almost indefinitely, but in this instance it was inhibited by the addition of ambucetamide.…”
Section: Resultssupporting
confidence: 91%
“…The " menstrual stimulant" is a plain-muscle stimulant of endometrial origin, overactivity of which is considered to be a possible cause of dysmenorrhoea (Chambers and Pickles, 1958;Pickles, 1959). It was therefore of interest to see whether ambucetamide antagonized the effect of menstrual stimulant on the human myometrium.…”
mentioning
confidence: 99%
“…The general types of effect on smooth-muscle preparations have been described before (Chambers & Pickles, 1958;Pickles, 1959b) and only the following additional facts need be noted here. Although all these stimulants caused contractions that were slow and persistent by comparison with those induced by histamine, the responses to component C were often delayed in onset by j-2 min and then 234 lllsom 0 SEPARATION OF MENSTRUAL MUSCLE STIMULANTS 235 persisted for 5 min or more, even after the stimulant had been washed out (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…It had previously been found (Pickles, 1959b) that no appreciable quantities of histamine, acetylcholine or 5-hydroxytryptamine, added to the initial acetone extract, passed into the crude lipid extract (then made with ether). A similar experiment showed that this was still true for histamine and 5-hydroxytryptamine when dichloromethane was used instead of ether, but that a small amount of acetylcholine could pass into the crude extract.…”
Section: H J Clitheroe and V R Picklesmentioning
confidence: 99%
“…Department of Physiology, University of Sheffield Human endometrial curettings and menstrual fluid contain lipoid substances that stimulate the myometrium in vitro. It is thought that these substances released in vivo would stimulate the myometrium and so facilitate the expulsion of the decidua menstrualis (Pickles, 1959).…”
Section: Oxfordmentioning
confidence: 99%